Research handbook on the sociology of law - Přibáň, Jiří, 1967-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2020)
"This unique Research Handbook maps the historical, theoretical, and methodological concepts in sociology of law, exploring the rich and complex nature of this area of research. It argues that sociology of law flourishes due to its strong capacity for interdisciplinary engagement and links to other scientific concepts, methodologies and research fields. Composed as a set of enquiries into the current state of sociology of law, expert contributions cover diverse themes such as inequality and discrimination, crime and punishment, and social justice. Reflecting on recent publications in law and society, socio-legal studies and interdisciplinary law research, the Research Handbook revisits the specific role of sociology of law, its disciplinary boundaries and its relationship to both legal and social sciences. The comprehensive nature of the Research Handbook on the Sociology of Law will appeal to law and social justice practitioners and scholars, as well as students in legal and social science fields who are looking to understand current trends and future research in the discipline"--
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: právní sociologie; sociologie; sociology of law; sociology; e-knihy online; e-books online